Internal structure of laboratory compacted warm mix asphalt (2012)
Warm mix asphalt (WMA) are asphalt mixtures fabricated at lower temperatures (i.e., 20 C to 50 C) than conventional hot mix asphalt (HMA). Therefore, as compared to HMA, WMA offer several engineering, economical, and environmental advantages. However, research is still required to identify the response, properties, and performance of WMA, since they still constitute a relatively new technology. This paper focuses on the analysis of the internal structure of WMA specimens compacted using both the Superpave Gyratory Compactor (SGC) and the Texas Gyratory Compactor (TxGC). This analysis was conducted in terms of the air voids (AV) characteristics assessed by applying X-ray Computed Tomography and image analysis techniques. The results obtained suggest that the addition of WMA additives and corresponding reduction of the compaction temperature for SGC specimens did not lead to significant changes in the vertical distribution of total AV content as compared to that of the control-HMA. However, some differences were reported in terms of the AV size, which suggests the existence of discrepancies in the aggregate packing condition. Therefore, additional research is suggested to fully validate the equivalence of the internal structure of both WMA and HMA.